ANALISIS PENGARUH HARGA, KUALITAS BUAH DAN LUAS LAHAN TERHADAP PENDAPATAN PETANI KELAPA SAWIT DI DESA MEKAR INDAH: Roni Hidayat, Suroto2, Hermansyah3 - Roni Hidayat; Suroto Suroto; Hermansyah Hermansyah (Politeknik Seruyan, 2025)
In Indonesia, oil palm is the main plantation product, this plant has a high economic value and makes a significant contribution to the country's foreign exchange earnings thanks to its main products, namely Crude Palm Oil (CPO) and Palm Kernel Oil (KPO). This study aims to 1) Analyze the effect of price on the income of oil palm farmers in Mekar Indah Village. 2) Analyze the effect of fruit quality on the income of oil palm farmers in Mekar Indah Village. 3) Analyze the effect of land area on the income of oil palm farmers in Mekar Indah Village. 4) Analyze the effect of price, fruit quality and land area on the income of oil palm farmers in Mekar Indah Village. The method used is a quantitative method using multiple linear regression analysis. The results obtained from this study are that simultaneously the variables of price, fruit quality and land area have a significant effect on the income of oil palm farmers in Mekar Indah Village. While partially the price and land area affect the income of farmers in Mekar Indah Village, while the quality of the land does not affect the income of farmers in Mekar Indah Village. Keywords: Palm Oil, Price, Fruit Quality, Land Area